The egg and the nest : obtaining information about the reproductive biology of Apteryx spp. (family: Apterygidae), a cryptic avian taxon, through eggshells : a thesis in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Ecology at Massey University, Palmerston North, New Zealand - Vieco Gálvez, David (Massey University, 2019)
The amniotic eggshell is a bioceramic that can endure the passing of time without major alteration to its physical structure. Not surprisingly eggshells have been found in numerous paleontological excavations around the world and have been used to identify the presence of major taxa and furthermore, to propose hypotheses on how extinct amniotes lived and nested. In the past decades the information that has been obtained solely through eggshells, ranges from inferences of a specie’s habitat, to diet, and nesting behaviours. This information can be obtained using techniques such as microscopy, stable isotopes, ancient DNA, allometry, physics and biochemistry. The possibility of making inferences about an organism’s biology using its eggshells make them an invaluable asset in biological research, as we can obtain information about species that are difficult to observe otherwise, that are endangered, or that are not even alive anymore. It may also allow a comparison of the conditions that affected a species or a group during evolutionary time. In addition, these studies can be done with eggshells obtained after hatching, therefore without compromising the welfare of the study animals. The genus Apteryx (commonly known as Kiwi) is an endemic taxon to the three main islands of New Zealand/Aotearoa. This genus presents five distinct species and several taxa (possible subspecies). Apteryx is a unique clade because of its many unusual characteristics, including that all its species are ground-dwelling nocturnal insectivores, are winter breeders and nest in ground burrows or hollowed trees. Apteryx also presents a unique eggshell that has been part of scientific debates since the 1960’s. The physical features of Apteryx eggshells such as eggshell porosity, thickness and overall gas exchange, do not fit in most allometric models. Hypotheses to address this phenomenon have explored answers in the Apteryx’s extremely long incubation period (74 days or more) and low basal metabolic rate, because these require lesser oxygen. Apteryx are also the only ratite that nest in ground burrows or hollowed trees; all other ratite species lay in scrape type nests. Another oddity of Apteryx is that this genus presents diverse incubation behaviours, with some species having single male incubation, and others male and female incubation, as well as co- operative and group incubation. The mating system of Apteryx has been suggested to be monogamous for some of the species; however, Apteryx females are bigger than males, and at least in two of the Apteryx species, the female does not contribute to incubation whatsoever, suggesting some degree of sex role reversal. This could mean that the mating system of Apteryx revolves around polyandry, or as it is the case of most ratites, promiscuity (or polygynandry). The importance of studying Apteryx lays in its rarity; it is a group of species that defies allometric predictions and presents a wide variety of unusual adaptations. In many respects, it could be said that Apteryx presents adaptations to a niche that in other ecological contexts has been filled by mammals. Terrestrial mammals, except for chiropterans, are naturally absent in New Zealand ecosystems giving the opportunity to birds, which are plentiful in New Zealand, to exploit these niches and adapt accordingly. The series of oddities in Apteryx makes it a “must study” species to explore evolutionary pathways and the extremes in evolution. All Apteryx species are under some category of endangerment and are within the top priorities of restoration and conservation programs in New Zealand, which makes non-invasive methods of study the only way to approach biological and evolutionary questions about the group. This makes the use of eggshells an ideal method to approach biological and reproductive questions in Apteryx. The nests of Apteryx can be easily identified during breeding and non-breeding seasons, and eggshells are frequent remains amongst unoccupied nests; making them accessible with minimal disturbance to the birds. In this thesis, I explored the gaps in knowledge regarding the allometric predictions for the Apteryx eggs and eggshells, re-testing many of these assumptions, considering that there are five species, and not three as was the common belief before 2003. I explored the eggshell using optical techniques (scanning electron microscopy and micro-computed tomography) and experimentally (by determining the water vapour conductance of the eggshell for three of the five species). I found that Apteryx eggshell thickness decreased from north to south, and so did the water vapour conductance, porosity was much higher than what was previously measured in all of the sampled species, and it was higher than the allometric predictions. I found that Apteryx eggs presented a mineral “cuticle” composed by triangular crystals only reported in the literature for the eggshells of a Theropod dinosaur from the early Cretaceous. Morphological characteristics of the eggshell have been used taxonomically by palaeontologists to identify species; I found that it is possible to distinguish between the currently accepted Apteryx species by comparing the eggshell thickness, porosity, cuticle thickness and mammillary area. I next looked at the thermal properties of eggs and nests, using Newton’s law of cooling; I determined the cooling rate of eggs and nests of Brown Kiwi (Apteryx mantelli) and compared it with those of other precocial bird species. I found that Brown Kiwi eggs do not have any adaptation towards heat retention. The nests, however, have good temperature buffering and heat retention capacity. The nest architecture allows the nest to remain cooler than environmental temperature during the day and warmer than environmental temperature at night, which is when the incubating parent leaves the nest to forage. Finally, I examined Apteryx mantelli’s mating system by extracting DNA from the chorioallantoic membrane of hatched eggshells from Operation Nest Egg, a conservation strategy for kiwi. I determined the degree of parentage of the membranes found in several radio- tagged males over a period of five years using fragment analysis, and eight different microsatellite markers. I used very cost-effective techniques that make this study highly replicable and adaptable to other species. I found that Brown Kiwi is not a genetic monogamous species, having multiple contributor parents to a particular nest within and between years. In conclusion, I found that this non-invasive methodology using eggshells of hatched or abandoned eggs is very valuable to study cryptic and endangered species. Therefore, I advocate for further studies of this type, as the information that can be gained about a wide range of species and species behaviours using eggshells, together with relatively cheap techniques is of immense value to science.
Keywords: Kiwis; Eggs; Nests; Reproduction; Eggshells; 310903 Animal developmental and reproductive biology